Das Volk sitzt zu Gericht Österreichische Justiz und NS-Verbrechen am Beispiel der Engerau-Prozesse 1945-1954 - Kuretsidis-Haider, Claudia (Studien Verlag, 2006)
From December 1944 until the end of March 1945, there existed a forced labour camp for Hungarian Jews in Engerau (today town district Petrzalka of the Slovakian capital Bratislava), which war part of the "Reich Defense Line" ("Wüdostwall"). There, more than 2000 Hungarian Jews had to work like slaves, digging up entrechments to "defend" the German Reich against the approaching soviet troops.Approximate 400 of the forced labourers died of exhaustion, deseases or were beaten to death by Viennese SA men.During the last days of WW II the camp was evacuated. A spezial detachment shot those were sic kor unfit to march, others were killed while the following footmarch to Bad Deutsch-Altenburg. Destination was the concentratio camp of Mauthausen.Those abominable crimes caused a series of legal proceedings in post war Austria against more than 70 accused - the so called "Engerau-trias". In five main trials between 1945 and 1954 against 21 defendants the Vienna "Peoples Court" - a spezial court with the task to punish nazi-crimes - imposed 9 death sentences and 1 life imprisonment.The publication analyzes the legal actions of this spezial court on the basis of the trial records located in the district court in Vienna, puts the proceedings in the lager context of the coping with the Nazi past by Austrian courts, but also in Austrian society, presents biographies of judges, attorneys and counsels of the trials, describes the coverage in the newspapers and gives attention to the gender-aspect and the reflection of the "Engerau-trials" in historiography.This is the first publication, which gives a systematic overview of the first ten years of the 2nd republic focussing post war judiciary in the soviet occupation zone and the archievements of Austrian judiciary in respect to punishing nazi-crimes on the basis of the most extensive Holocaust proceeding in Austria.